Peer Bullying Among High School Students: Turkish Version of Bullying Scale - Arslan, Nihan (Sakarya University, 2017)
The aim of study was to conduct the reliability and validity studies of the Turkish version of The Forms of Bullying Scale (FBS; Shaw at el., 2013). The Turkish form of the scale was applied on 357 high school students. Scale was examined by the reliability analysis and confirmatory factor analysis within the scope of the adaptation study. Analysis results showed that the uni-dimensional structure well fit (x²=198.22, sd=33, p=0.00, RMSEA=.11, NFI=.94, NNFI=.93, CFI=.95, IFI=.95, IFI=.95, SRMR=.61). Cronbach alfa reliability of the scale was .86. The scale can be used by experts in the field in order to determine whether or not bullying behaviors differ in terms of demographic factors. Research was discussed in the literature.
Keywords: Bullying; Peer Bullying; Confirmatory Analysis